The effect of different training frequency on bone mineral density in older adults. A comparative systematic review and meta-analysis - Zitzmann, Anna Lena; Shojaa, Mahdieh; Kast, Stephanie; Kohl, Matthias; von Stengel, Simon; Borucki, Diana; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Middeldorf, Stefan; et al. (Bone, 2022)
Exercise frequency is a key aspect of exercise protocols. In this systematic review and meta-analysis, we determined the effect of training frequency on (areal) bone mineral density (BMD) at lumbar spine (LS) and hip. Reviewing seven electronic databases up to April 2021, we conducted a systematic review of the literature according to the PRISMA statement. Inclusion criteria were (a) controlled exercise trials (b) with at least two study arms that compared low versus high exercise frequency, (c) an intervention ≥6 months and (d) BMD assessments at lumbar spine (LS) or hip. The analysis was conducted as a mixed-effect meta-analysis and used “type of exercise” and “study duration” as moderators in subgroup analyses. Standardized mean differences (SMD) for LS- and hip-BMD changes were defined as outcome measures. Seven studies with 17 exercise groups were included in the analysis. We observed significantly higher effects of high (≥2 sessions/week) vs. low net training frequency (1–<2 sessions/week) exercise on LS- (SMD 0.55, 95%-CI: 0.20–0.90) but not hip-BMD (0.19, −0.06 to 0.45). Study duration was found to be a significant moderator for the effect of training frequency at LS- but not hip-BMD. In parallel, the type of exercise moderately influences the effect of training frequency on LS- but not on hip-BMD. We observed a superior effect of higher net training frequency on BMD. Longer exercise exposition increases this effect. Considering e.g. holidays, indisposition or other temporary absence, exercise programs on osteoporosis should provide at least 3 sessions/week/year to allow a net training frequency of more than two sessions/week. Study registration: PROSPERO (CRD42021246804).
CRIS-Team Scopus Importer:2021-10-22
Keywords: Bone mineral density; Exercise; Guideline; Training frequency